2019
DOI: 10.1002/slct.201903673
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Highly Fluorescent Poly(methacrylic acid)‐Capped Silver Nanoclusters for the Specific Detection of Iron(II)

Abstract: This work presented an easy synthesis method for water‐soluble, green and fluorescent silver nanoclusters with poly (methacrylic acid) (AgNCs@PMAA) and preliminarily explored their ability to detect Fe2+ by measuring their fluorescence quenching. The acquired AgNCs@PMAA showed steady, selective, and highly sensitive detection of Fe2+. The Fe2+ detection limit for AgNCs@PMAA was 3 μM, and a linear relationship was observed at 5–150 μΜ ion concentration. AgNCs@PMAA had no biological toxicity and could be used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Cyan-emissive CuNCs (PCuNCs) were prepared by a simple approach using PMAA as a capping agent and ascorbic acid as a moderate reducing agent. PMAA, a common polyelectrolyte, as a template contains several -COOH groups capable of coordinating with Cu 2+ ions, while the presence of methyl groups in the side chain facilitates the stabilization and formation of metal nanoclusters [42,43]. The orange-emitting CuNCs (BCuNCs) were synthesized at room temperature using a hydrazine hydrate as a reducing reagent and BSA protein as a template for the construction of nanoclusters [41].…”
Section: Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyan-emissive CuNCs (PCuNCs) were prepared by a simple approach using PMAA as a capping agent and ascorbic acid as a moderate reducing agent. PMAA, a common polyelectrolyte, as a template contains several -COOH groups capable of coordinating with Cu 2+ ions, while the presence of methyl groups in the side chain facilitates the stabilization and formation of metal nanoclusters [42,43]. The orange-emitting CuNCs (BCuNCs) were synthesized at room temperature using a hydrazine hydrate as a reducing reagent and BSA protein as a template for the construction of nanoclusters [41].…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…The ideal probe should have high sensitivity for selectively detecting the target analyte [37,40,42]. With due consideration, the fluorescence responses of PCuNCs-BCuNCs towards ROS were monitored in solution under physiological conditions.…”
Section: Analytical Performance Of Pcuncs-bcuncs Towards Rosmentioning
confidence: 99%
“…[25,26] Remarkably, the use of scaffolds helps to prevent particle aggregation during nanocluster synthesis. Notably, most of these studies have reported the use of AgNCs as fluorescent probes for the detection of a wide range of analytes, such as metal ions [27] and organic compounds [28,29] with approaches relying on measuring fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%